Study of the Hearing Threshold of Dance Teachers - Nehring, Cristiane; Bauer, Magda Aline; Teixeira, Adriane (International Archives of Otorhinolaryngology, 2015)
Introduction High sound pressure levels can cause hearing loss, beginning at high frequencies.Objective To analyze the hearing thresholds of dance teachers.Methods This study had a cross-sectional, observational, prospective, and descriptive design. Conventional and high-frequency hearing evaluations were performed with dance teachers and subjects in the control group.Results In all, 64 individuals were assessed, 32 in the research group and 32 in the control group. Results showed that individuals in the research group had hearing loss at frequencies between 4 and 8 kHz, but no significant difference was found between groups. Frequency analysis showed that individuals in the control group had higher thresholds than individuals in the research group at the frequency of 0.25 kHz. In the control group, men showed higher thresholds than women at the frequency of 9 kHz.Conclusion A low prevalence of hearing loss was found, with no difference between teachers and subjects from the control group. No difference was found for hearing thresholds at high frequencies between groups. Results have been partially affected by sex.
Keywords: hearing; hearing loss; noise-induced; audiometry